Uncertainty Assessment for Field Development Study Using Monte Carlo Simulation on Salap Field Multilayer Gas Reservoir - Fahrezi Oktaviandi; Boni Swadesi; Dyah Rini Ratnaningsih (Journal of Petroleum and Geothermal Technology, 2022)
Uncertainty assessment for Field Development Study is often only carried out in a Deterministic Method by only creating scenario sensitivity based on theoretical assumptions without add subsurface risk factors. In the uncertainty assessment model, when a model is made with a variable that only has one value for each sensitivity is called the Deterministic Method. Meanwhile, when a model is made with a variable that has value in the form of a probability distribution, the method is called the Probabilistic Method. In the Probabilistic Method, the probability distribution is influenced by the risk factors, while in the Deterministic Method, these factors have no effect because the input value is only based on theoretical assumption. Uncertainty assessment for the Salap Field Development Study was carried out using the Probabilistic Method Monte Carlo Simulation. The results of the study provide the number of proven reservoirs, volume in place, volume of resources, number of development wells, plateau production period and field life that already accommodates subsurface risk factors and uncertainty in geological-reservoir data. The paper also compares the assessment result between the Probabilistic Method with the Deterministic Method to see how risk factors influenece the study results.